PENGGUNAAN MIKROKONTORLER ATMEGA 8535 SEBAGAI KONTROL CAS AKI DIGITAL - Zulkifli Zulkifli (Jurnal Informatika Global)
The development of technology and science in the field of microcontroller progress rapidly growth and many of the utilized to assist in human life. This development was marked by a growing number of tools created with microcontroller based digital technology to replace the work of the equipment manual. This is due to the use of the microcontroller can ease the work and has a fairly high level of precision, as well as assisted with the use of LCD (Liquid Crystal Display) as a display that will show the results of the pengecasan tool in running, the microcontroller used in this circuit is the ATMEGA 8535 Key words : Mkirokontroler, ATMEGA 3585, LCD